An investigation on spray cooling using saline water with experimental verification. (15th January 2016) - Sadafi, M.H.; González Ruiz, S.; Vetrano, M.R.; Jahn, I.; van Beeck, J.; Buchlin, J.M.; Hooman, K.
Highlights: Using saline water in spray cooling is investigated numerically and experimentally. Phase Doppler Interferometry is used to validate the model. Non-dimensional analysis is performed on results. Two dimensionless correlations for cooling performance and wet length are presented. Abstract: A natural draft dry cooling tower rejects heat in a power plant. Spray cooling of the inlet air to the cooling tower improves the total efficiency of the power plant. To overcome the scarcity of natural water sources, this research is studying the usage of saline water in spray assisted dry cooling towers. A nozzle is analysed experimentally. It is shown that the CFD model captures the spray well. A full cone spray is simulated in a vertical cylindrical domain representative of cooling tower flows. To investigate the influences of initial and ambient conditions on the spray performance, fourteen different cases are simulated and trends analysed. It is shown that the distances from the nozzle, after which the dry stream starts (wet lengths), are in the range of 4.3–5.25 m depending on the test conditions. A dimensionless study is performed on the wet length and cooling efficiency as the two main parameters. Finally, to predict the wet length and cooling efficiency, two dimensionless correlations are presented and their impact on cooling tower operation is discussed.